2006
DOI: 10.1038/nn1818
|View full text |Cite
|
Sign up to set email alerts
|

Coherent motion of stereocilia assures the concerted gating of hair-cell transduction channels

Abstract: The hair cell's mechanoreceptive organelle, the hair bundle, is highly sensitive because its transduction channels open over a very narrow range of displacements. The synchronous gating of transduction channels also underlies the active hair-bundle motility that amplifies and tunes responsiveness. The extent to which the gating of independent transduction channels is coordinated depends on how tightly individual stereocilia are constrained to move as a unit. Using dual-beam interferometry in the bullfrog's sac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 22 publications
3
93
0
Order By: Relevance
“…Optical measurements confirmed that the bundle moves as a unit even up to high frequencies [12,14], at least for small deflections (<50 nm). On the other hand, video measurements of chick hair cells [9] suggested that stereocilia do not move uniformly, and some modeling efforts have assumed that only tip links hold stereocilia together [15].…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Optical measurements confirmed that the bundle moves as a unit even up to high frequencies [12,14], at least for small deflections (<50 nm). On the other hand, video measurements of chick hair cells [9] suggested that stereocilia do not move uniformly, and some modeling efforts have assumed that only tip links hold stereocilia together [15].…”
Section: Introductionmentioning
confidence: 67%
“…Thus all channels get essentially the same stimulus. If elements other than tip links hold stereocilia tightly together, then transduction channels are mechanically in parallel [12,14]. With a force stimulus, the parallel arrangement of channels can lead to positive cooperativity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result indicates that reverse electromechanical transduction is not responsible for subdiffusion. To test whether BAPTA or any of the other drugs caused hairbundle damage, we used a dual-beam laser interferometer directed at the opposite edges of the hair bundle (20) and established that after the pharmacological treatments the stereociliary movements remained coherent, ruling out gross rearrangements of bundle geometry as the cause of the cessation of subdiffusion. Moreover, in line with previous observations (21,22), damaged hair bundles that became incoherent produced a broad spectrum of subdiffusive behaviors regardless of any pharmacological treatments.…”
Section: Resultsmentioning
confidence: 99%
“…1C,D; [11]). This unitary movement of the bundle is significantly less dissipative than the displacement pattern with relative motion [10].…”
Section: Introductionmentioning
confidence: 99%